Model Pembelajaran Quantum Teaching unnjk Meningkatkan Hasil Belajar IPS Kdas V SDS Kalam Kudus Kecamatan Tebing Tinggi, Kabupaten Bengkalis - Salman, Marwoto (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
Quantxil Teaching Study Mode to increase the result of studyin IPS subject score for class V SDS Kalam Kudus Tebing Tinggi district,Bengkalis regency. The subjects of this research are 30 students in classV C SDS Kalam Kudus, which are consist of 14 females and 16 malesmdents. The measured variable is student activity, teacher activity whichis measured by using observation sheet and study result by writing test.Base on the result of this research, it can be concluded that QuantumTeaching Study Mode can increase student score in IPS subject at SDSKalam Kudus Selatpanjang.Keyrword : Quantum Teaching Study Mode, Score